Clinical and history features of patients with recurrent deep endometriosis: A retrospective study - Daria N. Senina; Saadat A. Pashaeva; Yuliya A. Kulakova; Vladimir D. Chuprynin; Aleksandra V. Asaturova; Larisa S. Ezhova; Natalia A. Buralkina (IP Berlin A.V., 2024)
Aim. To identify clinical and history features of patients with recurrent deep endometriosis (RDE). Materials and methods. A retrospective study of clinical and history data of 200 patients with DE undergoing surgical treatment at the Department of General Surgery of the Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology in 2020-2021. Group 1 included 80 patients with RDE, group 2 included 120 patients with newly diagnosed DE. All patients underwent surgical treatment followed by immunohistochemical examination and DE confirmation. Results. An association was found between the young age of the patient at the time of the first surgery and the type of endometriosis. It was found that women with a history of endometriosis surgery in early reproductive years (29.22±5.3 years) are at risk of recurrent endometriosis. Two or more surgeries were reported in 33.7% of RDE patients. In 90.2% of patients, endometriosis recurred with clinical manifestations; in 9.8%, it was asymptomatic and diagnosed on pelvic ultrasound. The group of RDE patients showed a longer period of infertility (5.432±3.53 years) than the group with newly diagnosed DE (2.953±1.29 years). It was found that the surgeries performed in RDE patients were longer, more complex, and associated with more blood loss. Intestinal resection, ureterolysis, adhesiolysis, and salpingectomy were significantly more common in the RDE group than in patients without a history of endometriosis surgery. Conclusion. In most cases, RDE is clinically manifested, rarely asymptomatic and diagnosed by visualization methods. Patients with a history of surgery at a younger age are at risk of RDE, and their surgical interventions are more complicated with more blood loss. Currently, surgical treatment of DE is the optimal method; however, it has serious disadvantages with severe and even life-threatening postoperative complications.